2014
DOI: 10.1039/c4ee00038b
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid solar-redox scheme for liquid fuel and hydrogen coproduction

Abstract: A ferrite based oxygen carrier promoted with a mixed ionic–electronic conductor support is used in a hybrid solar-redox scheme. Based on both experiments and simulations, this scheme has the potential to co-produce liquid fuel and hydrogen from methane and solar energy at high efficiency with near zero life cycle CO2 emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…As can be seen, equilibrium P O2 of Fe/FeO redox pair, which is a commonly used redox material, is away from the ideal (high performance) region for the hybrid solar-redox scheme. This is confirmed by a number of studies that reported low syngas selectivity and limited CO 2 conversions ( 16 , 34 38 ). Thermodynamic analysis suggests that no first-row transition metal oxide has redox properties located in this region ( 39 ).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…As can be seen, equilibrium P O2 of Fe/FeO redox pair, which is a commonly used redox material, is away from the ideal (high performance) region for the hybrid solar-redox scheme. This is confirmed by a number of studies that reported low syngas selectivity and limited CO 2 conversions ( 16 , 34 38 ). Thermodynamic analysis suggests that no first-row transition metal oxide has redox properties located in this region ( 39 ).…”
Section: Resultssupporting
confidence: 72%
“…To address this challenge, we proposed a hybrid solar-redox scheme for water splitting, wherein concentrated solar energy is used to drive the reduction reaction in the presence of methane (CH 4 ) that undergoes partial oxidation (POx) to produce Fischer-Tropsch (F-T) ready syngas. Using perovskite-supported Fe 3 O 4 as the redox material, up to 77% steam-to-hydrogen conversion was achieved ( 16 , 36 ). Although such a methane-assisted solar-thermal water-splitting scheme is applicable for CO 2 splitting, further increases in water/CO 2 -splitting conversion is desirable from process efficiency and product separation standpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, chemical looping studies use O 2 from air as an oxidant to recuperate the oxygen mobile material [26,27], and recent studies have also used steam [28]. Because of the poorer oxidative nature of CO 2 when compared to these two oxidants, maintaining the phase stability of the oxygen carrier is desired because less energy is required to re-oxidize an oxygen vacant material as opposed to recovering its crystalline phase.…”
Section: Introductionmentioning
confidence: 99%
“…As a support, mixed ionic and electronic conductive (MIEC) perovskites such as La 1Àx Sr x FeO 3 (LSF) have shown to enhance the redox activity of iron oxides by nearly two orders of magnitude [51][52][53][54]. Perovskite and perovskite supported iron oxide have also been explored as redox catalysts for syngas generation and water-splitting [42,56]. In terms of CLOU applications, La containing perovskite supports are reported to be effective to enhance the oxygen donation properties of mixed Mn-Fe and Co-Fe oxides [23].…”
Section: Introductionmentioning
confidence: 99%